Brain metastasis from primary peritoneal carcinoma: Case report and literature review. (June 2017) - Liu, Xuan; Masuoka, Jun; Ebashi, Ryo; Koguchi, Motofumi; Inoue, Kohei; Ogata, Atsushi; Takase, Yukinori; Nakahara, Yukiko; Shimokawa, Shoko; Kawashima, Masatou; Yoshihara, Masahiro; Abe, Tatsuya
Highlights: Primary peritoneal carcinoma (PPC) is a rare malignancy arising from the extraovarian peritoneum. We present a patient with PPC who developed an isolated and single brain metastasis. The serum CA 125 level was increased before the brain metastasis became symptomatic. An optimal treatment after resection of a single brain metastasis requires further study. Abstract: Here, we describe a patient with primary peritoneal carcinoma (PPC) who developed a late, solitary brain metastasis. It is a case of a 68-year-old female presented with a 1-month history of progressive gait disturbance who had undergone a surgical resection of PPC five years prior, followed by adjuvant chemotherapy. An MRI revealed a 4.6 cm mass lesion in her right cerebellum. The patient underwent total removal of the tumour. The histopathology was consistent with a brain metastasis due to PPC. This condition is a rare malignancy of peritoneum, and only six cases of brain metastasis have been reported in PPC patients to date. Due to the prolongation of survival resulting from advanced chemotherapy for PPC, more patients will live long enough to develop brain metastases.